A mucoactive drug carbocisteine ameliorates steroid resistance in rat COPD model. (August 2016) - Song, Yun; Yu, Ping; Lu, Juan-Juan; Lu, Hao-Zhong; Zhu, Liang; Yu, Zhi-Hua; Chen, Hong-Zhuan; Cui, Yong-Yao
Abstract: Steroid insensitivity has been commonly found in chronic obstructive pulmonary disease (COPD) patients, which is mediated by the reduction of histone deacetylase (HDAC) 2. Here we aimed to establish a steroid resistant model on experimental COPD rats and evaluate the effect of carbocisteine (S-CMC), a mucoactive drug. Exposure to cigarette smoke (CS) caused marked pathological features of COPD which are insensitive to DEX associated with the down-regulation of HDAC2 expression/activity. The DEX insensitivity observed in COPD featured rats was improved by S-CMC in the aspects of inhibiting chronic lung inflammation (total and differential inflammatory cell counts, inflammatory cytokines release and inflammatory cells infiltration); ameliorating airway remodeling (thickness of airway epithelium and smooth muscle, airway fibrosis, and the level of α-SMA and TGF-β1); improving emphysema (emphysema index D2, level of MMP-9 in BALF and the expression of alpha-1 antitrypsin) and preventing impairments of lung function (PEF, IP and IP-slope). Simultaneously, down-regulation of HDAC2 expression/activity was ameliorated by S-CMC treatment. These results indicate that the rat COPD model with steroid resistance was established by active smoking in a short time frame and demonstrate that the failure of steroid therapy can be restored by S-CMC accompanied by increasing HDAC2 expression/activity, providing additional evidence that S-CMC might be used for GC resistance in COPD.